Kinematic Analysis and Trajectory Planning of Redundant Mobile Manipulators - Xia Guangjian; Zeng Qingsheng; Feng Dongyan; Li Shenlin (Jixie chuandong)
A method based on the polynomial interpolation combined with the segmental planning was proposed for the trajectory planning of redundant mobile manipulators. The kinematic analysis was carried out by considering the manipulator and the mobile platform as an integrated system, a generalized form of the geometric Jacobi matrix and its pseudo-inverse were derived. In the trajectory planning process, the trajectory running time and the spatial distance travelled by the end of the mobile manipulator were taken as the optimization objectives, the velocity and acceleration constraints of each joint were also taken into account, and a genetic algorithm was used to optimize the trajectory of the redundant mobile manipulator. The simulation results demonstrate that the trajectory of the optimized motion is smooth, and the displacement and velocity curves of the joints of the mobile platform and the manipulator are continuous and stable, which verifies the feasibility and effectiveness of the method.